EFFICACY OF METHOTREXATE VERSUS AZATHIOPRINE IN THE TREATMENT OF CHRONIC ACTINIC DERMATITIS: A RANDOMIZED CONTROL TRIAL - Paracha, Mohammad Majid; Gandapur, Hina Zahoor; Orakzai, Abdul Qayyum; Sahibzad Mahmood Noor; Farah Sagheer (Journal of Ayub Medical College Abbottabad, 2022)
Background: Azathioprine is first line immunosuppressive agent in treatment of chronic actinic dermatitis. The role of methotrexate has been effective in different dermatosis and it seems reasonable to use it in the treatment of chronic actinic dermatitis. Aims: We sought to compare the efficacy of methotrexate versus azathioprine in treatment of chronic actinic dermatitis. Methods: Patients with chronic actinic dermatitis were randomized to receive methotrexate in group A and azathioprine in group B. The response to treatment in terms of percentage PASI reduction and side effects of medications were assessed 12 weeks follow-up. Results: In group A, the percentage PASI reduction was <25% in 2 (1.19%) patients, 25-49% in 47 (27.9%) patients, 50-74% was achieved by 35 (20.8%) patients while in group B, the percentage PASI reduction of 25% was achieved by 2 (1.19%) patients, 25-49% in 45 (26.7%) patients, 50-74% in 37 (22.0%) patients. More than or equal to 75 percentage PASI reduction was not achieved by any patient in the study. Both drugs were found efficacious in treatment of CAD. A total of 23 (27.38%) patients in group A and 22 (26.19%) patients in group B showed derangement in laboratory investigations during 12 weeks treatment. The limitation of study was inability to do photo-patch test, so patients were diagnosed clinically and biopsy was done in clinically challenging cases. Conclusion: This study shows that methotrexate is equally effective as azathioprine in the treatment of chronic actinic dermatitis with its added benefits of being cost effective and better safety profile.